Nanopore diameters tune strain in extruded fibronectin fibers - Raoufi, Mohammad; Das, Tamal; Schön, Ingmar; Vogel, Viola; Brüggemann, Dorothea; Spatz, Joachim P. (Nano letters, 2015)
Fibronectin is present in the extracellular matrix and can be assembled into nanofibers in vivo by undergoing conformational changes. Here, we present a novel approach to prepare fibronectin nanofibers under physiological conditions using an extrusion approach through nanoporous aluminum oxide membranes. This one-step process can prepare nanofiber bundles up to a millimeter in length and with uniform fiber diameters in the nanometer range. Most importantly, by using different pore diameters and protein concentrations in the extrusion process, we could induce varying lasting structural changes in the fibers, which were monitored by Förster resonance energy transfer and should impose different physiological functions.
Gesehen am 10.06.2020